The clinical and genetic findings in a Chinese family with Axenfeld-Rieger syndrome. Issue 12 (December 2022) - Cheng, Lingyan; Zhang, Yinong; Ding, Yuzhi; Yuan, Zhilan; Han, Xiao
Abstract: Objecive: To describe the clinical and genetic findings of an Axenfeld-Rieger syndrome (ARS) family with a new PITX2 splicing mutation. Methods: A Chinese ARS family with five affected individuals was recruited. Exome sequencing was performed on the proband and the variant ( C.253-9C > A) in PITX2 gene was detected as a pathogenic mutation. Sanger sequencing was performed for verification and cosegregation analysis. Real-time polymerase chain reaction (RT- PCR) and Western blotting were performed to verify the expression of the pathogenic gene. Results: All the patients showed abnormalities in the anterior segment of both eyes including posterior embryotoxon, corectopia, iris dysplasia, and iridocorneal tissue adhesions. In addition, they all presented systemic features, including maxillary hypoplasia, underbite, hypodontia, conical teeth. Only III-7 showed obvious umbilical skin. In the PITX2 family, we identified a novel heterozygous splicing mutation (C.253-9C > A) which was confirmed by Sanger sequencing to be completely cosegregated with the ARS phenotype. Real-time quantitative PCR and Western results showed that PITX2 mRNA and protein expression were significantly lower in patients compared with unrelated normal controls. Conclusion: In the ARS pedigree, we summarized the variable phenotype, described a novel PITX2 splicing mutation which expand the genetic spectrum of ARS. We further confirmed the possibility of development of ARS induced by this PITX2 gene deficiency. Abstract : Axenfeld-rieger syndrome; Exome sequencing; PITX2 splicing mutation.